Detection of metastases in breast cancer patients - Dose-Schwarz, J.; Mahner, S.; Schirrmacher, S.; Jenicke, L.; Müller, V.; Habermann, C. R.; Brenner, W. (Nuklearmedizin - NuclearMedicine, 2008)
Distant metastases at primary diagnosis are a prognostic key factor in breast cancer patients and play a central role in therapeutic decisions. To detect them, chest X-ray, abdominal ultrasound, and bone scintigraphy are performed as standard of care in Germany and many centers worldwide. Although FDG PET detects metastatic disease with high accuracy, its diagnostic value in breast cancer still needs to be defined. The aim of this study was to compare the diagnostic performance of FDG PET with conventional imaging. Patients, methods: A retrospective analysis of 119 breast cancer patients who presented for staging was performed. Whole-body FDG-PET (n=119) was compared with chest X-ray (n=106) and bone scintigraphy (n=95). Each imaging modality was independently assessed and classified for metastasis (negative, equivocal and positive. The results of abdominal ultrasound (n=100) were classified as negative and positive according to written reports. Imaging results were compared with clinical follow-up including follow-up imaging procedures and histopathology. Results: FDG-PET detected distant metastases with a sensitivity of 87.3% and a specificity of 83.3%. In contrast, the sensitivity and specificity of combined conventional imaging procedures was 43.1% and 98.5%, respectively. Regarding so-called equivocal and positive results as positive, the sensitivity and specificity of FDG-PET was 93.1% and 76.6%, respectively, compared to 61.2% and 86.6% for conventional imaging. Regarding different locations of metastases the sensitivity of FDG PET was superior in the detection of pulmonary metastases and lymph node metastases of the mediastinum in comparison to chest x-ray, whereas the sensitivity of FDG PET in the detection of bone and liver metastases was comparable with bone scintigraphy and ultrasound of the abdomen. Conclusions: FDG-PET is more sensitive than conventional imaging procedures for detection of distant breast cancer metastases and should be considered for additional staging especially in patients with high risk primary breast cancer.
Keywords: Breast cancer; staging; FDG-PET; metastasis